Pelaksanaan Akad Mukhabarah - Yuli Kartika Hutasuhut; Risalan Basri Harahap (IAIN Padangsidimpuan, 2022)
This research is motivated by the existence of cooperation between land owners and rice cultivators in Tano Tombangan District, Angkola South Tapanuli, namely a land owner gives his fields to be managed to rice cultivators on the basis of trust and mutual agreement, on a voluntary basis, without any suggestion of coercion. The main problem in this study is how the implementation of the Mukhabarah contract in the Panindoan Tano Village of Tombangan Angkola and how the Compilation Review of Sharia Economic Law regarding the implementation of the Mukhabarah contract in the Panindoan Tano Village of Tombangan Angkola. This type of research uses the field research method (field research) and is sourced from primary data and secondary data. The data collection technique used in this research is interviews. The results showed that the implementation of the Mukhabarah contract in managing rice fields with a cultivator agreement would provide yields to the land owner after calculating the total amount of harvest obtained. However, it is not in reality that the cultivators tell how much they have harvested, but only submit the harvest that is part of the land owner. Thus, it means that there is a broken promise from the cultivator to the land owner against the agreement in the contract made between the cultivator and the land owner, so the land owner feels disadvantaged. The review of Sharia Economic Law on the implementation of the Mukhabarah contract in Panindoan Tano Village, Tombangan Angkola, is not in accordance with the compilation of Sharia Economic Law as stated in Article 260 which does not explain the estimated yield of the crop to the land owner as a whole.